ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN INDUSTRI TEKSTIL YANG GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2010-2012 - Yulian, Tri Nurindahyanti; Rahman, Kristanti (JURNAL EKONOMI, 2016)
This study aims at analyzing the ratio PER, ROA, and DER through stock price in textile industry company. In this case the researcher uses financial statements data of the textile company listed on the Indonesian Stock Exchange. The researcher uses 10 textile company listed in Indonesian Stock Exchange in 2010-2012 by using purposive random sampling. The data are from financial statements published in Indonesian Stock Exchange.The results study shows that Y = 5,585 + 0,293X1 + 0,143 X2 + 0,211 X3 if Y without any influence of X1, X2, and X3 is constant, it is 5,585. If X1 increases a unit, Y will increase in 0,293 units, if X2 increases in a unit, Y will increase in 0,143 units, if X3 increases in a unit, Y will increase in 0,211 units.Based on the analysis of the data, it can be concluded that the variables PER influence through stock price, ROA, and DER does not influence in stock price.Keywords : PER, ROA, and DER